The given expression cannot be simplified.
Chat with our AI personalities
7 plus 7x--2x plus 3 is: 7 + 7x + 2x + 3 = 0 9x + 10 = 0 9x = -10 x = -10/9 = -1 1/9
1
x2 + 7x + 9 = 3 ∴ x2 + 7x + 6 = 0 ∴ (x + 6)(x + 1) = 0 ∴ x ∈ {-6, -1}
It is: x-1+4+7x-3 = 8x simplified
7x + y + z = 6 7x + y + 4z = 9 y + x = 6 Take the first two statements and subtract them. 7x + y + z = 6 7x + y + 4z = 9 _____________ 0 + 0 - 3z = -3 Therefore: z = 1 Then you are left with: 7x + y + 1 = 6 7x + y + 4 = 9 which is impossible, so this is an impossible equation.